Halal Certification for Non-Muslim-Owned Restaurants in Brunei Darussalam: Regulatory Practice, State Mufti Opinions, and Imam al-Nawawī’s Juristic Perspective - Mahmud, Hafini bin; Kurniawan, Cecep Soleh; Mohiddin, Hajah Mas Nooraini binti Haji (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2026)
Halal certification is a central institutional mechanism for strengthening Muslim consumer confidence in restaurants and food premises within Brunei Darussalam. Although halal logo is widely perceived as an assurance of lawful consumption, a critical legal and juristic question of whether halal certification requires the restaurant owner to be a Muslim remains. Therefore, this study aims to examine the practical implementation of halal certification for non-Muslim-owned restaurants in Brunei Darussalam relative to State Mufti opinions and the juristic reasoning attributed to Imam al-Nawawī within the Shāfiʿī legal tradition. A library-based method was used with a qualitative design. Data were collected from classical fiqh texts, contemporary fatwa, national legislation, administrative regulations, and relevant policy documents. The collected materials were then analyzed through content analysis to identify normative arguments, regulatory standards, and points of legal tension. The results showed that Brunei current administrative practice allows halal certification for restaurants owned by non-Muslims under specific procedural and supervisory conditions. However, a significant inconsistency was found between the operational policy and the State Mufti juristic position, particularly concerning ownership, authority over food preparation, and the reliability of compliance. By integrating regulatory analysis with classical jurisprudence, the results contribute to the broader discourse on halal governance, Islamic legal authority, and contemporary policy implementation in Muslim-majority states. In conclusion, this study underscores the need for clearer regulatory harmonization between state fatwa institutions and halal certification agencies to ensure legal coherence and sustained public trust.